Formation Process of Particles and Cloud Condensation Nuclei Over the Amazon Rainforest: The Role of Local and Remote New‐Particle Formation. Issue 22 (17th November 2022) - Zhao, Bin; Fast, Jerome; Shrivastava, Manish; Donahue, Neil M.; Gao, Yang; Shilling, John E.; Liu, Ying; Zaveri, Rahul A.; Gaudet, Brian; Wang, Shuxiao; Wang, Jian; Li, Zeqi; et al.
Abstract: Understanding the formation processes of particles and cloud condensation nuclei (CCN) in pristine environments is a major challenge in assessing the anthropogenic impacts on climate change. Using a state‐of‐the‐art model that systematically simulates the new‐particle formation (NPF) from condensable vapors and multi‐scale transport of chemical species, we find that NPF contributes ∼90% of the particle number and ∼80% of the CCN at 0.5% supersaturation (CCN0.5%) in the pristine Amazon boundary layer during the wet season. The corresponding contributions are only ∼30% and ∼20% during the dry season because of prevalent biomass burning. In both seasons, ∼50% of the NPF‐induced particles and ∼85% of the NPF‐induced CCN0.5% in the boundary layer originate from the long‐range transport of new particles formed hundreds to thousands of kilometers away. Moreover, about 50%–65% of the NPF‐induced particles and 35%–50% of the NPF‐induced CCN0.5% originate from the downward transport of new particles formed aloft. Plain Language Summary: Aerosol particles affect Earth's climate partly by acting as the seeds for cloud droplet formation, called cloud condensation nuclei (CCN). It is important to understand the processes that control the particle and CCN concentrations in pristine environments, such as the Amazon rainforest, because the radiative forcing of climate is estimated using the pristine conditions as a baseline. However, these processes are still poorly understood. Here we quantify them using a state‐of‐the‐art atmospheric model. This model is configured with advanced treatment of the initial formation of particles from condensable gases, termed new‐particle formation (NPF), as well as a state‐of‐the‐art treatment of horizontal and vertical transport of chemical species across different spatial scales. We find that NPF contributes ∼90% of the particle number and ∼80% of the CCN in the pristine Amazon boundary layer during the wet season. About half of the NPF‐induced particles and up to 85% of the NPF‐induced CCN in the boundary layer originate from the long‐range transport of new particles formed hundreds to thousands of kilometers away. About 50%–65% of the NPF‐induced particles and 35%–50% of the NPF‐induced CCN originate from the downward transport of new particles formed at high altitudes (>2 km). Key Points: New‐particle formation (NPF) contributes ∼90% of the particle number and ∼80% of the cloud condensation nuclei (CCN) at 0.5% supersaturation in the pristine wet‐season Amazon boundary layer About 85% of the NPF‐induced CCN in the boundary layer is contributed by new particles formed hundreds to thousands of kilometers away About 35%–50% of the NPF‐induced CCN originates from the downward transport of new particles formed at high altitudes (>2 km)